Manajemen Krisis Public Relations PT. X Kota Pekanbaru pada Pengunduran Haji dan Umrah di Era Pandemi Covid-19 - Laranty Irabella; Maman Chatamallah (UPT Publikasi Ilmiah Unisba, 2021)
Abstract. This research is entitled “Public Relations Crisis Management of PT. X (Case Study of Public Relations Crisis Management of PT. X Pekanbaru City on Hajj and Umrah Withdrawals in the Era of the Covid-19 Pandemic)